Methods for quantifying rain-splash dispersal of Neonectria ditissima conidia in apple canopies - Campbell, Rebecca E.; Wallis, D. Roger; Walter, Monika (Frontiers in Horticulture, 2023)
Many microorganisms can be dispersed by rain-splash, whereby spores become suspended in water and are spread via droplets. The resulting dispersal gradient is dependent on several factors including rainfall intensity, the nature of the plant canopy and its effects on splash, deposition, redistribution (secondary splash) and filtering. Gradients of spore dispersal with distance are important for understanding epidemics, and the primary dispersal gradient can shape an epidemic for several pathogen generations. However, microorganisms are difficult to trap, identify and enumerate efficiently. This makes it difficult to study the spread and dispersal of pathogens to aid in biosecurity responses and management of epidemics. We used macroconidia of Neonectria ditissima, the causal organism of apple canker, to explore patterns of rain-splash dispersal in tree canopies. We investigated the use of a fluorescent tracer dye, PTSA (1,3,6,8-pyrenetetrasulfonic acid), as a surrogate to conidia capture during natural and artificial rain events, and lens tissue as ‘surrogate leaves’ to recapture tracer dye. Conidia and dye were released from central point sources 2.5 m above the ground and recaptured in passive rainwater traps or artificial ‘leaves’. Quantile regression and exponential models were used to explore variation and dispersal gradients derived for both conidia and dye, with and without tree canopy and with natural or artificial precipitation. Estimated dispersal gradients were steeper with a flatter tail when no tree canopy was present, whereas presence of tree canopy resulted in more variation and shallower predicted dispersal gradients, with fatter tails, predicting potential dispersal to further distances from the source. The majority of conidia and dye were recaptured at less than 1 m from the source, but small concentrations of spores were detected up to 3 m and dye more than 6 m. High variation in natural conditions requires further investigation to fully quantify natural dispersal gradients. Nevertheless, these results show the merit of tracer dye, artificial leaves, and quantile regression as tools to estimate potential dispersal patterns of N. ditissima and other rain-splash dispersed microorganisms, considering rain-splash factors in real canopies and natural situations for predicting inoculum dispersal.